Membadankan (Embodying) Narasi dan Spiritualitas: Analisis Performativitas Seni Relief Pendopo Teras Candi Panataran Berdasarkan Konsep Embodiment - Rochman, Luthfan Nur; Ashari, Chaidir (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This article examines the narrative reliefs of the Pendopo Teras at Panataran Temple as an active visual-spatial medium that shapes the religious experience of its visitors. Using a qualitative-descriptive method and an interpretive approach within the framework of social archaeology, the study applies Rosemary A. Joyce’s concept of embodiment to interpret the reliefs as material-discursive action. The analysis focuses on the arrangement of the reliefs, the prasawya reading direction, the depiction of figures, gestures, attributes, and their relation to architectural elements. The findings show that the reliefs of the Pendopo Teras not only represent the stories of Panji, Sri Tanjung, Sang Satyawan, and Bhubuksah-Gagangaking, but also embody social status, emotion, asceticism, desire, and purification as performative experience. Accordingly, the Terrace Pavilion may be understood as an introductory space that prepares pilgrims physically and spiritually before entering the more sacred spaces of the temple complex. Artikel ini membahas relief naratif pada Pendopo Teras Candi Panataran sebagai medium visual-spasial yang aktif membentuk pengalaman religius pengunjung. Dengan menggunakan metode kualitatif-deskriptif dan pendekatan interpretatif dalam kerangka arkeologi sosial, kajian ini menerapkan konsep embodiment Rosemary A. Joyce untuk menafsirkan relief sebagai tindakan material-diskursif. Analisis difokuskan pada susunan relief, arah baca prasawya, penggambaran tokoh, gestur, atribut, dan relasinya dengan elemen arsitektural. Hasil kajian menunjukkan bahwa relief-relief Pendopo Teras tidak hanya merepresentasikan kisah Panji, Sri Tanjung, Sang Satyawan, dan Bhubuksah-Gagangaking, tetapi juga membadankan status sosial, emosi, asketisme, hasrat, dan penyucian sebagai pengalaman performatif. Dengan demikian, Pendopo Teras dapat dipahami sebagai ruang pengantar yang mempersiapkan peziarah secara fisik dan spiritual sebelum memasuki ruang candi yang lebih sakral.